2013
DOI: 10.1002/2013jc009157
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification in the three oceans surrounding northern North America

Abstract: [1] The uptake of anthropogenic CO 2 drives ocean acidification, with attendant effects on the saturation state of calcium carbonate (X) and marine ecosystems. Here, we examine ocean acidification within the context of large-scale water mass exchange and local physical and biogeochemical processes along a section around northern North America. Waters in the North Pacific are preconditioned by the global-scale circulation to be low X source waters and as they move northward across the Bering and Chukchi seas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 72 publications
1
38
0
1
Order By: Relevance
“…Timmermans et al 2013b, figure 5.24c). 2009;Mathis et al 2011;Yamamoto-Kawai et al 2013). It is of note that trends in Beaufort Gyre heat YAMAMOTO-KAWAI In recent years, ocean acidification has emerged as one of the dominant issues in marine science, particularly in highlatitude regions, where its progression has been greater than many other ocean basins (e.g., Fabry et al 2009;Steinacher et.…”
Section: ) Freshwater Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Timmermans et al 2013b, figure 5.24c). 2009;Mathis et al 2011;Yamamoto-Kawai et al 2013). It is of note that trends in Beaufort Gyre heat YAMAMOTO-KAWAI In recent years, ocean acidification has emerged as one of the dominant issues in marine science, particularly in highlatitude regions, where its progression has been greater than many other ocean basins (e.g., Fabry et al 2009;Steinacher et.…”
Section: ) Freshwater Contentmentioning
confidence: 99%
“…Since 2008, dozens of comprehensive ocean acidification projects have been conducted in the Arctic by a number of nations, including the United States, Canada, Sweden, Japan, South Korea, China, and Germany, with a commensurate increase in understanding of the controls on ocean acidification. In a seminal paper on the changing carbonate chemistry of the Arctic Ocean, Yamamoto-Kawai et al (2009) showed that increasing sea ice melt water in the Canada Basin is causing a sharp reduction in Ω in the surface waters due to the dilution effect on calcium carbonate ions. Several other processes, such as melting sea ice, terrestrial and marine organic matter respiration, and upwelling are exacerbating the effects of ocean acidification, leading to rapid changes in the marine environment.…”
Section: ) Freshwater Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the winter portion of this seasonal pattern is still not well understood, due mostly to a sampling bias arising from the logistical challenge of winter measurements. The lack of carbonate system observations through the fall, winter, and particularly early spring, has led to different interpretations about how biogeochemical processes affect the ability of seasonally ice‐covered Arctic seas to act as a CO 2 sink (Else et al, ; Miller et al, ; Shadwick et al, ; Yager et al, ) and uncertainty about their influence on carbonate saturation states (Fransson et al, ; Yamamoto‐Kawai et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…4e and h), having been 20 upwelled from beyond the shelf-break onto the shelf. This bottom layer is sourced from the UHL where a DIC maximum consistently resides beyond the shelf-break (Anderson et al, 2010;Yamamoto-Kawai et al, 2013). The UHL source-water is of Pacific-origin, and is preconditioned before entering the Arctic to have low Ω Ar values (Yamamoto-Kawai et al, 2013).…”
Section: Ocean Acidificationmentioning
confidence: 99%